2007
DOI: 10.1245/s10434-006-9345-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Very Young Korean Breast Cancer Patients Have Worse Outcomes?

Abstract: Compared with older premenopausal Korean women with breast cancer, those younger than 35 years old had a poorer prognosis as a result of a higher rate of recurrence, a later stage at diagnosis, and more aggressive disease. Thus, in Korean breast cancer patients, age younger than 35 years was an independent predictor of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
5
23
1
1
Order By: Relevance
“…Although being younger than 35 at diagnosis was associated with poorer DSS in NHW and black patients, it was not associated with DSS in HW patients or Asian patients. Our study also showed that there was no survival difference in Asian subgroups when compared patients younger than 35 with 35–39, which is consistent with the studies conducted in Japan (Yoshida et al , 2011) and Korean (Kim et al , 2007). This may suggest that, in HW and Asian groups, tumour biology and age are independent prognostic factors for survival.…”
Section: Discussionsupporting
confidence: 92%
“…Although being younger than 35 at diagnosis was associated with poorer DSS in NHW and black patients, it was not associated with DSS in HW patients or Asian patients. Our study also showed that there was no survival difference in Asian subgroups when compared patients younger than 35 with 35–39, which is consistent with the studies conducted in Japan (Yoshida et al , 2011) and Korean (Kim et al , 2007). This may suggest that, in HW and Asian groups, tumour biology and age are independent prognostic factors for survival.…”
Section: Discussionsupporting
confidence: 92%
“…Young women with breast cancer tend to have more advanced tumor TNM staging, more invasive pathological type, higher tumor grade, higher lymph node positivity, higher proportion of triple-negativity, higher HER2 expression and lower ER/PR positivity [1322]. A multivariate analysis [23], including the age at diagnosis, tumor size, lymph node status, tumor grade, year of treatment, protocol allocation, and expected mortality, found that even if multiple impact factors were adjusted, the breast cancer diagnosed at a young age was closely associated with an increased risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…Les données concernant le lien entre âge, taille tumorale, atteinte ganglionnaire et statut HER2 sont plus controversées [4,7,41,59,83,94,171], avec des discordances qui, pour le dernier paramètre, peuvent être rapportées aux techniques de mesure qui ne sont pas homogènes pour les études les plus anciennes. Il a également été retrouvé une plus grande incidence des formes infl ammatoires chez les femmes plus jeunes [31].…”
Section: Généralités Particularités Biologiques Des Cancers Du Sein Dunclassified